Inclusive charged particle distributions in deep inelastic scattering events at HERA - Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Zhang, H; Bari, G; Basile, M; Bellagamba, L; et al. (1996)
A measurement of inclusive charged particle distributions in deep inelastic ep scattering for γ*p centre-of-mass energies 75 < W < 175 GeV and momentum transfer squared 10 < Q2 < 160 GeV2 from the ZEUS detector at HERA is presented. The differential charged particle rates in the γ*p centre-of-mass system as a function of the scaled longitudinal momentum, xF, and of the transverse momentum, pt* and <pt*2>, as a function of xF, W and Q2 are given. Separate distributions are shown for events with (LRG) and without (NRG) a rapidity gap with respect to the proton direction. The data are compared with results from experiments at lower beam energies, with the naive quark parton model and with parton models including perturbative QCD corrections. The comparison shows the importance of the higher order QCD processes. Significant differences of the inclusive charged particle rates between NRG and LRG events at the same W are observed. The value of <pt*2> for LRG events with a hadronic mass MX, which excludes the forward produced baryonic system, is similar to the </pt*2></pt*2>